OP33 Exposure-Based Assessment of Modal Travel Risk in England Using Routine Health Data. (17th September 2012) - Mindell, JS; Leslie, D; Wardlaw, M
Abstract : Background: Cycling can make large contributions to population health but perceived road danger is a strong disincentive to cycling. Research on cycling safety is distorted by not making like-for-like comparisons. We examined age- and sex-specific deaths and injuries in England by travel mode, considering both the ICD external codes included in official travel risk data and those excluded but required for accurate comparative assessment, to provide more precise comparisons of travel risks by mode. Methods: ICD–10 external codes were grouped by type of incident for pedestrians, cyclists, and car/van drivers; the fourth digit was used to exclude non-transport casualties. Numbers of hospital admissions, from Hospital Episodes Statistics data, and deaths in England 2007–2009 were obtained for these ICD codes, by age-group and sex. Aggregated per capita distance travelled by age-group, sex and mode in England from National Travel Survey for each year 2007–2009, weighted to be nationally-representative, was multiplied by the estimated mid-year population. Time spent travelling was estimated using mean trip speeds by mode. We calculated fatal injury and hospital admission rates by distance travelled and by time spent travelling by age-group, sex, and travel mode. 95% confidence intervals for Poisson parameters were calculated using the formulae for weighted sums. Results: Fatalities per million hours' use (f/mhu) varied little (0.15–0.45f/mhu by mode for men, 0.09–0.31f/mhu for women). Risks were similar for men aged 21–49 years for all three modes and for female pedestrians and drivers aged 21–69 years. The group most at risk for each mode were: male drivers aged 17–20 years (1.3f/mhu, 95% CI 1.2, 1.4); male cyclists aged 70 years or older (2.2 f/mhu, 1.6, 3.0) and female pedestrians aged 70 years or older (0.95 f/mhu, 0.86, 1.1). In general, fatality rates were substantially higher amongst males than females, except for drivers aged 60 years or older. Risks per hour for male drivers under 30 years were similar or higher than for male cyclists; for 17–20 year olds the risk was higher for drivers (33/Bn km, 95% CI 30, 36; 1.3f/mhu, 1.2, 1.4) than cyclists (20/Bn km, 10, 37; 0.24f/mhu, 0.12, 0.45) using distance or time. Conclusion: This is the first study in the UK to provide travel casualty rates by distance travelled and per hour, by mode, by age-group and sex, based on nationally-representative data, to enable unbiased intermodal comparisons for population sub-groups. Males aged 17–20 years old face higher risks as drivers than as cyclists, and do not achieve better safety as drivers until over 30 years. Not making like-for-like comparisons sustains the misleading stereotype that cycling is relatively hazardous.